Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.14715/cmb/2018.64.9.3
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor as an important possible component of novel therapy for cancer, diabetes and cardiovascular diseases

Abstract: Nerve growth factor (NGF) is protein discovered by Rita Levi Montalcini in the 1950s. It plays a crucial role in the development of nervous system. NGF may be produced by a variety of cells even beyond nervous system. NGF modulate cell metabolism by binding to p75NTR and TrkA receptors. NGF is involved in psychological processes and may be the possible therapeutical agent for diabetes, cancer and cardiovascular diseases, which will be described in the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Increasing evidence suggest that in addition to their neurotrophic functions, proNGF and NGF participate in several biological processes, including the immune response, inflammatory response, pulmonary hypertension, wound healing and cancer metastasis ( 23 , 33 , 36-42 ). Studies on NGF and its receptors have identified novel therapeutic approaches for malignant tumors, diabetes, chronic wounds and cardiovascular diseases ( 13 , 40 ).…”
Section: Biology Of Ngf and Its Receptorsmentioning
confidence: 99%
“…Increasing evidence suggest that in addition to their neurotrophic functions, proNGF and NGF participate in several biological processes, including the immune response, inflammatory response, pulmonary hypertension, wound healing and cancer metastasis ( 23 , 33 , 36-42 ). Studies on NGF and its receptors have identified novel therapeutic approaches for malignant tumors, diabetes, chronic wounds and cardiovascular diseases ( 13 , 40 ).…”
Section: Biology Of Ngf and Its Receptorsmentioning
confidence: 99%
“…Neurotrophins including nerve growth factor (NGF) family and brain derived neurotrophic factor (BDNF) are small polypeptides with potent effects on health and well-being of the neuronal and non-neuronal cells. 4 , 5 Recently, NGF and BDNF as adipokines are taken into consideration due to their possible roles in some metabolic disorders such as diabetes mellitus 6 , 7 , atherosclerosis 8 and metabolic syndrome (MetS). 9 Despite the contradictory results 10 , the growing body of evidence suggests that low levels of circulating BDNF and NGF were significantly associated with high body mass index (BMI), hemoglobin A1C (HbA1C) and hypertriglyceridemia.…”
Section: Introductionmentioning
confidence: 99%